2009
DOI: 10.1063/1.3050096
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anisotropic poly(vinyl alcohol) hydrogel by small- and ultra-small-angle neutron scattering

Abstract: Poly͑vinyl alcohol͒ ͑PVA͒ hydrogels are formed from PVA solution when physical cross-links form during freeze/thaw cycling. By applying a stress during the freeze/thaw process, PVA hydrogels with anisotropic mechanical properties are produced. We have used small-and ultra-small-angle neutron scattering to study the structure at length scales of 2 nm to 10 m. By supplementing the neutron data with data from atomic force microscopy, we have probed a large range of length scales within which structural changes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This changed the microstructure of the PVA-C, causing the crystallites to orient in the direction of the stress. Details of the nanostructure of the anisotropic PVA-C have been studied using SANS and USANS [11]. Differences for tensile properties between the longitudinal and perpendicular directions increased as the initial strain applied after the first cycle was increased.…”
Section: Cardiovascular Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This changed the microstructure of the PVA-C, causing the crystallites to orient in the direction of the stress. Details of the nanostructure of the anisotropic PVA-C have been studied using SANS and USANS [11]. Differences for tensile properties between the longitudinal and perpendicular directions increased as the initial strain applied after the first cycle was increased.…”
Section: Cardiovascular Devicesmentioning
confidence: 99%
“…The solution is then thawed back to room temperature leading to the formation of a solid gel-PVA-C. The micro-/ nanostructure of PVA-C has been examined through several techniques including transmission electron microscopy (TEM) [9], small angle X-ray scattering (SAX) [9] and small angle and ultrasmall angle neutron scattering (SANS and USANS) [10,11]. Observations conclude that the first freeze-thaw cycle (FTC) produces polymer-rich regions due to the formation of ice crystals in the amorphous regions [10,12].…”
Section: Processing Parameters For Pva-c Preparationmentioning
confidence: 99%
“…[80][81][82][83] In some cases,the compression-or stretching-induced deformation remains in place without in situ polymerization owing to the plastic nature of the system. [84][85][86][87] As al imitation of this method, the precursor isotropic hydrogels must withstand large forces so that their gel networks undergo sufficient deformation.…”
Section: Hydrogels With Oriented Polymer-chain Networkmentioning
confidence: 99%
“…That being said, the use of hydrogels as cryoprotectants for cells in conjunction with cryogelation processes has been demonstrated to successfully create cell-loaded macroporous gel scaffolds, albeit with some loss of cell activity following the freezing process. [70] Furthermore, although the rates of heating and cooling and the number of freeze/thaw cycles conducted can at least in part be used to rationally control the pore size and distribution generated, [71,72] the generated pores still typically have a broad pore size distribution and minimal if any directionality. Tam et al have demonstrated the possible benefits of adding typical cryoprotectant carbohydrates such as d-galactose, d-glucose, d-trehalose, or d-sucrose to the pre-gel solution, as all these sugars interact with water to alter the nature of ice crystallization and thus create more transparent hydrogels with improved pore size control.…”
Section: Cryogelationmentioning
confidence: 99%